Entrepreneurial prospects for tuber crops technologies in India - Sivakumar, P Sethuraman; Mohan, Raji J; Byju, G (Indian Horticulture, 2025)
The tropical tuber crops including cassava, sweet potato, yams, elephant foot yam, taro, arrowroot, and Chinese potato have played a significant role in ensuring food and nutritional security in tribal areas, but they now stand at a crossroads. The growing transition toward healthy eating and disciplined lifestyles, along with a strong political will for self-reliance, has reshaped the role of tropical tubers in the country. Among them, cassava contributes substantially to industrial production, particularly through starch and sago, while sweet potato is emerging as a healthy food that provides balanced nutrition for both children and adults. Elephant foot yam and greater yam have established themselves as commercial vegetables with stable market prices. In contrast, minor tubers such as arrowroot and Chinese potato serve niche industrial applications as well as direct consumption markets.